2013
DOI: 10.1038/srep03331
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nanofoam carbon and re-emergence of Superconductivity in compressed CaC6

Abstract: Pressure can tune material's electronic properties and control its quantum state, making some systems present disconnected superconducting region as observed in iron chalcogenides and heavy fermion CeCu2Si2. For CaC6 superconductor (Tc of 11.5 K), applying pressure first Tc increases and then suppresses and the superconductivity of this compound is eventually disappeared at about 18 GPa. Here, we report a theoretical finding of the re-emergence of superconductivity in heavily compressed CaC6. The predicted pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…8). Despite the fact that the metal valences are different in LiC 6 (Pmmn) and a previously predicted metastable phase of CaC 6 [110], these two compounds have identical crystal structures. Although these lithium carbides are not thermodynamically stable, they are metastable with all positive phonon frequencies.…”
Section: B Diverse Carbon Structuresmentioning
confidence: 79%
“…8). Despite the fact that the metal valences are different in LiC 6 (Pmmn) and a previously predicted metastable phase of CaC 6 [110], these two compounds have identical crystal structures. Although these lithium carbides are not thermodynamically stable, they are metastable with all positive phonon frequencies.…”
Section: B Diverse Carbon Structuresmentioning
confidence: 79%
“…It should be also noted that the critical temperature of CaC 6 can be further modified with increasing pressure. Many theoretical and experimental investigations proved that T C in CaC 6 exhibits an interesting increasing-decreasingincreasing behavior under pressure [18,[20][21][22][23][24]. In particular, the critical temperature increase linearly to the value of 15.1 K, when the pressure increases to 7.5 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently however, Li et al have reported the reemergence of the superconductivity in the heavily compressed CaC 6 (p 39 GPa), applying pressure via the theoretical calculations [24]. In particular, the authors have stated that the predicted phase III (space group Pmmn) with the formation of the carbon nanofoam is found to be stable at a wide pressure range with the critical temperature up to 14.7 K at 78 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of BCS superconductors have been theoretically proposed161718 as the development of computational crystal structure prediction tools1920 and methods. In this paper, we perform a systematic search for thermodynamically stable calcium bismuth at ambient and high pressure by using the variable-composition ab initio evolutionary algorithm212223 and density functional theory (DFT).…”
mentioning
confidence: 99%